AMALAN-AMALAN DI BULAN RAJAB: SUNNAH DAN BID’AH - Ritonga, Muhammad Tohir (HIBRUL ULAMA, 2024)
This study aims to explain the practices in the month of Rajab: sunnah and bid'ah. This type of research is a type of literature study with a qualitative approach to interpret the text of the hadith using the hadith analysis approach. The results of the study indicate that there are several worships that are recommended to be performed during the month of Rajab, although with general evidence. Some of the evidence is weak and Muslims should increase worship. However, if there are many weak hadiths, they can be hasan li ghairih, moreover, some scholars state that it is okay to make the evidence of weak hadiths in the virtue of charity, as long as the weakness is not too great. The heresy explained in this paper includes the Raghaib prayer, although some scholars include this worship in their books, there is no evidence that can be used as a guideline in practicing it. However, this can be replaced with the intention of performing the sunnah awwabin prayer and others.